Cortisol, testosterone and mood state variation during an official female football competition - Casanova, N.; Palmeira-De Oliveira, A.; Pereira, A.; Crisóstomo, L.; Travassos, B.; Costa, A. M. (The Journal of Sports Medicine and Physical Fitness, 2016)
BACKGROUND: Endogenous hormones are essential on the control of physiological reactions and adaptations during sport performance. This study aims to compare the mood state and the salivary levels of cortisol and testosterone during an official female association football tournament.